Serum miRNAs Expression and SNAP-25 Genotype in Alzheimer’s Disease - Agostini, Simone; Mancuso, Roberta; Liuzzo, Gaia; Bolognesi, Elisabetta; Costa, Andrea Saul; Bianchi, Anna; Clerici, Mario (Frontiers in aging neuroscience, 2019)
MicroRNAs (miRNAs) are small non-coding RNAs that control gene expression by binding their 3' untranslated region (3'UTR) region; these molecules play a fundamental role in several pathologies, including Alzheimer's disease (AD). Synaptosomal-associated protein of 25 kDa (SNAP-25) is a vesicular protein of soluble -ethylmaleimide-sensitive factor attachment protein receptor (SNARE) involved in neural plasticity and in the exocytosis of neurotransmitters, processes that are altered in AD. Recent results showed that a reduction of SNAP-25 is associated with dementia, and that the rs363050 SNAP-25 polymorphism correlates with cognitive decline and brain atrophy, as well as with the outcome of multistructured rehabilitation in AD patients. We verified the presence of possible correlations between the serum concentration of miRNAs that bind the SNAP-25 3'UTR region and AD. Six different microRNAs (miR-181a-5p, miR-361-3p, miR-23a-3p, miR-15b-3p, 130a-3p and miR-27b-3p) that bind the SNAP-25 3'UTR region were measured by qPCR in serum of AD patients ( = 22), mild cognitive impairment (MCI) subjects ( = 22) and age- and sex-matched controls ( = 22); analysis of results was done stratified for the rs363050 SNAP-25 genotype. Results showed that miR-27b-3p, miR-23a-3p and miR181a-5p serum concentration was significantly reduced in rs363050 SNAP-25 GG homozygous AD patients. Notably, concentration of these miRNAs was comparable in rs363050 AA homozygous AD patients, MCI and healthy controls (HCs). Data herein suggest that miRNAs that bind the SNAP-25 3'UTR region interact with SNAP-25 polymorphisms to influence the neural plasticity typical of AD brains, possibly as a consequence of modulatory activity on SNAP-25 mRNA and/or protein.